2019
DOI: 10.7759/cureus.4125
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Traumas and Paradigm Shifts: The Necessary Adaption of the Steerable Microcatheter in Pediatric Interventional Radiology

Abstract: The use of traditionally available intra-arterial devices have historically been designed with the adult patient population in mind. Currently, there are not manufactured devices specifically tailored for use during pediatric interventional procedures, pressuring interventional operators to adapt commonplace and readily available devices for interventional management. Experienced interventional operators understand that pediatric and adult interventions can entail vastly different management, affecting patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A small number of studies have reported cases in which a steerable microcatheter with a distal diameter of 2.4-F (SwiftNINJA standard; Sumitomo Bakelite, Tokyo, Japan) was directly advanced via the femoral approach to a target organ without a diagnostic catheter, achieving successful arterial intervention: hepatic arterial infusion chemotherapy, uterine artery embolization, and arterial embolization for pediatric trauma [2] , [3] , [4] . The steerable tip of a steerable microcatheter plays a key role in increasing the operability of these interventions [2] .…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have reported cases in which a steerable microcatheter with a distal diameter of 2.4-F (SwiftNINJA standard; Sumitomo Bakelite, Tokyo, Japan) was directly advanced via the femoral approach to a target organ without a diagnostic catheter, achieving successful arterial intervention: hepatic arterial infusion chemotherapy, uterine artery embolization, and arterial embolization for pediatric trauma [2] , [3] , [4] . The steerable tip of a steerable microcatheter plays a key role in increasing the operability of these interventions [2] .…”
Section: Discussionmentioning
confidence: 99%